Teaching Mathematics Through The Game Method Of The Knowledge Orbit (Texas Journal of Multidisciplinary Studies, 2026)
This article discusses the content, advantages and possibilities of using the game method "Knowledge Orbit", which is considered one of the innovative pedagogical technologies in teaching mathematics, in the educational process. This method serves to increase students' interest in science, develop logical thinking, and effectively master knowledge. Also, the evaluation criteria and practical application mechanisms of lessons organized based on the method are analyzed.